Low Frequency Bimorph Cantilever Energy Harvester For Pacemaker Applications - Mostafa, Abdelrahman Mostafa Khalaf (2020)
A Master of Science thesis in Biomedical Engineering by Abdelrahman Mostafa Khalaf Mostafa entitled, “Low Frequency Bimorph Cantilever Energy Harvester for Pacemaker Applications”, submitted in May 2020. Thesis advisor is Dr. Lufti Albasha. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).